Approximation of a positive random variable distribution by the mixture of exponential distsibutions - Valakevičius, Eimutis (Lietuvos matematikos rinkinys, 1998)
In the paper is proposed a method how to approximate the model of non-markovian stochastic system by markovian one with a countable space of states and continuous time.